The benefits of elaborative encoding over retrieval practice for associative learning. - Jaeger, Antônio; Martins, Thuan Henrique Pedrosa Gomes; Rodrigues, João Pedro Parreira; Muniz, Bruno Felipe Barbosa; da Silveira Fonseca, Ana Luísa Santiago; de Oliveira Gonçalves, Ariel (Memory & Cognition, 2025)
The practice of retrieval has been shown to be highly beneficial for memory retention, but it has seldom been compared with learning strategies other than repeated study. Here, we compared the benefits of retrieval practice (without feedback) with the benefits of two elaborative encoding tasks for word pair learning. Specifically, after studying series of randomly combined word pairs, participants performed an interactive-imagery (Experiments 1–2) or sentence-generation task (Experiments 3–5), retrieval practice, and a letter-counting or a rereading task. In Experiments 1–4, the word pairs were shown after a 24-h interval for testing in its original form or with the second word replaced by the second word from another pair, and participants performed recognition (old/new) followed by associative memory tests (intact/rearranged). In Experiment 5, memory was tested in a final cued-recall task administered shortly after initial learning. The interactive-imagery task was as beneficial as retrieval practice for recognition, but consistently more beneficial than retrieval for performance at the associative task. Sentence generation, on the other hand, produced greater performances than retrieval practice in recognition, associative memory, and cued-recall tests. These findings reveal that simple elaborative encoding tasks, such as imagining scenes or generating sentences, can be more beneficial for memory retention than retrieval practice without feedback.